Analisis Siklus APBD pada Dinas Perindustrian dan Tenaga Kerja Kota Surabaya - Dzakiyah, Annisa Aliyyatud; Zahra, Bilqist Nabila; Angeli G. F, Nadya; Debi W., Nanda (SUSTAINABLE, 2024)
The analysis of regional financial management is a systematic study of all financial activities carried out by local governments in the context of governance and development. The Surabaya City Department of Industry and Labor is one of the local government agencies focused on the fields of industry and labor. This study aims to analyze the implementation of the Regional Budget (APBD) cycle at the Surabaya City Department of Industry and Labor. This research is relevant given the importance of effective and efficient regional financial management in supporting the development of the industrial and labor sectors. The research method used is descriptive qualitative, with data collection through document studies, in-depth interviews, and observation. The results of the study indicate that, in general, the Surabaya City Department of Industry and Labor has implemented the APBD cycle in accordance with applicable regulations.